2011
DOI: 10.1016/j.psc.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization and Poor Reassurance: Potential Predictors of Somatoform Disorders

Abstract: Objective Somatoform disorders are common conditions, but the current diagnostic criteria are considered to be unreliable, based largely on medically unexplained symptoms. DSM-5 is considering other possible characteristics of somatizers including high utilization, dissatisfaction with care, and poor response to reassurance. This paper reviews the available literature for evidence to support these criteria, and evaluates if distinctive aspects of these characteristics exist in somatizers. Methods The Pubmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Contrary to what was hypothesized based on the IMHA, reassurance-seeking did not lead to alienation. This inconsistency may be due to the fact that the items used to measure reassurance-seeking reflect a more passive desire for health-related reassuranceseeking, which stands in contrast to the active, incessant, and aversive reassurance-seeking, as it is conceptualized by the IMHA and other theories (Puri & Dimsdale, 2011). Taking account of the perceptual factor (absorption) in our analysis, results showed that absorption was positively related to worry and reassurance-seeking.…”
Section: Discussionmentioning
confidence: 81%
“…Contrary to what was hypothesized based on the IMHA, reassurance-seeking did not lead to alienation. This inconsistency may be due to the fact that the items used to measure reassurance-seeking reflect a more passive desire for health-related reassuranceseeking, which stands in contrast to the active, incessant, and aversive reassurance-seeking, as it is conceptualized by the IMHA and other theories (Puri & Dimsdale, 2011). Taking account of the perceptual factor (absorption) in our analysis, results showed that absorption was positively related to worry and reassurance-seeking.…”
Section: Discussionmentioning
confidence: 81%
“…However, the association between somatoform disorders and FA is in keeping with a large body of evidence from elsewhere [20][21][22]. In fact it has recently been suggested that a redrawing of the diagnostic criteria for the category somatoform disorders is needed, focusing on its main attributes: somatic symptoms, excess concern with symptoms and illness and abnormal health care utilization [34].…”
Section: Association Between Psychiatric Disorders and Fa In Family Pmentioning
confidence: 71%
“…This revealed differences across women in terms of the importance to them of achieving reductions in cancer risk—those who were concerned over cancer recurrence had stronger preferences for management strategies associated with lower ongoing risks. Previous research has found high levels of healthcare utilisation among patients who exhibit high levels of concern about disease symptoms or illness (Barsky, Orav, & Bates, ; Bermingham, Cohen, Hague, & Parsonage, ; Mewton & Andrews, ; Puri & Dimsdale, ). It is plausible that women who are concerned about cancer recurrence following breast cancer treatment might use more healthcare services than those who are not similarly concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Three attributes, risk of pain, risk of losing breast sensitivity and OOP for CPM surgery, were specific to the CPM option (see Table 1). The range of attributes and possible levels were refined following a pilot survey with 87 women recruited from an online general community panel provider (PureProfile, 2014).…”
Section: Routine Monitoring Onlymentioning
confidence: 99%